The Ideology of the State and Direction of Development as the Foundation of Public Policy: Islamic Perspective - Maesaroh, Imas (Nursyam Center, 2023)
Pancasila, Indonesia's fundamental ideology, was declared during the presidency of Soekarno and subsequently solidified by Soeharto, continuing to influence the administrations of Habibie, Gus Dur, Megawati, Susilo Bambang Yudhoyono, and Joko Widodo. Throughout its history, Pancasila has evolved into both a moral and practical basis for the nation's development. In the era of the New Order, Indonesia implemented the Garis-Garis Besar Haluan Negara (GBHN) as a comprehensive development plan with short–, medium–, and long-term goals aimed at achieving national welfare. This plan laid the groundwork for subsequent administrations, such as Susilo Bambang Yudhoyono and Joko Widodo, to execute the Plan of National Development Medium Term (RPJMN) for the periods of 2010-2014 and 2014-2019. Looking ahead, Indonesia will soon adopt the New National Development Plan (2019-2024) with ambitious goals, including eradicating poverty, eliminating hunger, improving healthcare, and enhancing the quality of education. All these development plans are firmly rooted in Pancasila as the foundational ideology of the Indonesian state. Both Pancasila and the National Development Plan serve as the cornerstone for formulating and constructing public policies in Indonesia. From an Islamic perspective, public policy aligns with the concept of maslahah al-ammah, which refers to the general benefit or welfare of the people. This overarching concept encompasses principles such as legal certainty, equal rights, balanced rights and obligations, professionalism, fair treatment, transparency, accountability, targeted support for vulnerable groups, efficiency, speed, and affordability. These principles are inherently guided by Islamic teachings, ensuring that public policies are in harmony with the values of justice and social welfare.